Critical Success Factors (CSF) of tree planting in Malaysia - Ab Sani, Jasasikin; Mohamed Mustafar, Atikah; Othman, Noriah; Hj. Baharuddin, Zainul Mukrim (Association of Malaysian Environment-Behaviour Researchers (AMER); ABRAmalaysia, 2018)
Specific critical success factor (CSF) assessment element for tree planting should be produced to monitor construction work in Malaysia. This paper prepared to investigate quality control of tree planting in Malaysia based on their CSF. This study used a mixed-method approach to collecting data. There were 225 Landscape Architect respondents successfully responded to the survey conducted. The outcome of this paper began with the assessment elements that had to be rated by respondents according to their general assumption on the critical level of each element. Then, it followed with the mean comparison of assessment elements based on four influencing factor.